2019
DOI: 10.1002/adfm.201904112
|View full text |Cite
|
Sign up to set email alerts
|

XBi4S7 (X = Mn, Fe): New Cost‐Efficient Layered n‐Type Thermoelectric Sulfides with Ultralow Thermal Conductivity

Abstract: We report a new class of cost-efficient n-type thermoelectric sulfides with a layered structure, namely MnBi4S7 and FeBi4S7. Theoretical calculations combined with synchrotron Xray/neutron diffraction analyses reveal the origin of their electronic and thermal properties. The complex low-symmetry monoclinic crystal structure generates an electronic band structure with a mixture of heavy and light bands near the conduction band edge, as well as vibrational properties favorable for high thermoelectric performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 92 publications
1
16
0
Order By: Relevance
“…The elastic parameters, including the average sound velocity v a , Young’s modulus E , Poisson ratio v ρ , and Grüneisen parameter γ, can be calculated using the equations given in the SI. The v a values of Pt 3 Bi 4 S 9– x Se x in the range of 1454–1921 m/s are close to those of other Bi chalcogenides listed in Table , and also comparable with those of renowned thermoelectric materials with low thermal conductivities such as BiCuSeO (2107 m·s –1 ), AgSbTe 2 (1727 m·s –1 ), and CsAg 5 Te 3 (1774 m·s –1 ) . Based on the measured sound velocities, the Debye temperatures (Θ D ) of the four compounds are calculated to be 205.9, 188.2, 169.4, and 170.4 K, respectively, which are also comparable with those of the other materials shown in Figure b and Table .…”
Section: Resultssupporting
confidence: 78%
“…The elastic parameters, including the average sound velocity v a , Young’s modulus E , Poisson ratio v ρ , and Grüneisen parameter γ, can be calculated using the equations given in the SI. The v a values of Pt 3 Bi 4 S 9– x Se x in the range of 1454–1921 m/s are close to those of other Bi chalcogenides listed in Table , and also comparable with those of renowned thermoelectric materials with low thermal conductivities such as BiCuSeO (2107 m·s –1 ), AgSbTe 2 (1727 m·s –1 ), and CsAg 5 Te 3 (1774 m·s –1 ) . Based on the measured sound velocities, the Debye temperatures (Θ D ) of the four compounds are calculated to be 205.9, 188.2, 169.4, and 170.4 K, respectively, which are also comparable with those of the other materials shown in Figure b and Table .…”
Section: Resultssupporting
confidence: 78%
“…Based on the energy equipartition principle, heat capacity from the acoustic and optical branches will be C / n 1 and C ( n 1 ‐1)/ n 1 , respectively. Therefore, with an increase in n 1 , the contribution of acoustic phonons is depressed, and lower κ lat values are achieved, which has been confirmed in many thermoelectric materials with complex crystal structures 117–123 . Additionally, researchers have found that the heat capacity of mid‐temperature liquid‐like Cu 2 Se gradually decreases with an increase in temperature 124–126 .…”
Section: Heat Transport Modelsmentioning
confidence: 79%
“…The more structured DOS associated with a low-dimensional structure has stimulated efforts to increase the Seebeck coefficient by tuning the Fermi level to sharp discontinuities in the DOS [683], although reductions in thermal conductivity due to interface scattering of phonons appears to play a more dominant role. One-dimensional chain structures [684] and two-dimensional structures, including intercalates of dichalcogenides, A x TiS 2 (A = Co, Cu, Ag) [685][686][687] and a variety of pavonite-related materials [688,689], have been investigated, together with materials possessing low-dimensional structural motifs within a 3D structure, as exemplified by the derivatives of shandite, Co 3 Sn 2 S 2 .…”
Section: Sulfide and Selenide Thermoelectricsmentioning
confidence: 99%